2016
DOI: 10.1149/2.0381605jes
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbonate Ion Species on Direct Ammonia Fuel Cell Employing Anion Exchange Membrane

Abstract: The effect of carbonate ion species on the direct ammonia fuel cell (DAFC) employing anion exchange membrane (AEM) was evaluated. The OH-form and HCO 3 -form AEMs were applied as electrolytes for DAFCs. The obtained current density of DAFC with HCO 3 -form AEM was 1/7 of that with OH-form AEM. This is because carbonate ion species in the AEM suppress the ammonia oxidation reaction on Pt/C anode. Under the presence of carbonate ion species in the electrolyte, the ammonium ion and carbamate ion were formed accom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…OCV of ca. 0.45 V for 100% NH 3 (RH100%), see Table S1), 14,17,31 indicating that at this condition, the influence of the NH 3 oxidation reaction at the anode catalyst can be considered to be negligible. A closer look at Figure 1, however, shows that the current density was slightly improved when the small amount (less than 7%) of NH 3 was contained in the fuel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…OCV of ca. 0.45 V for 100% NH 3 (RH100%), see Table S1), 14,17,31 indicating that at this condition, the influence of the NH 3 oxidation reaction at the anode catalyst can be considered to be negligible. A closer look at Figure 1, however, shows that the current density was slightly improved when the small amount (less than 7%) of NH 3 was contained in the fuel.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the reduction in the activity of HOR in the presence of CO 2 -derived anion species causes serious degradation in the fuel cell performance 30 . 31 To understand the fundamental degradation mechanism, in situ observation of the Pt catalyst surface during the electrochemical reaction was performed by using attenuated total reflection infrared spectroscopy (ATR-IR). Furthermore, the effect of coexistence of NH 3 and HCO 3 − was studied extensively using both in situ ATR-IR and electrochemical methods.…”
mentioning
confidence: 99%
“…In recent years, developing energy storage and supply systems combined with renewable energies such as solar cells and windpowered electricity have attracted attention to utilize renewable energies effectively, 1 since environmental and energy problems, known as global warming and the depletion of fossil fuels, became critical issues. Direct-type fuel cell (DFC), where alcohols [2][3][4][5][6] and hydrogen-containing small molecules [7][8][9][10][11][12][13][14][15][16][17] are used as fuels, is one of the candidates of environmental friendly and efficient energy supply systems. DFC has similar constitution to the polymer electrolyte fuel cell (PEFC), 18,19 which consists of five components, electrolyte membrane, anode for electro-oxidation of fuels, cathode for oxygen reduction reaction (ORR), anode and cathode bipolar plates.…”
Section: Introductionmentioning
confidence: 99%
“…As a fuel for DFC, hydrogen carrier molecules hydrogenated by surplus renewable energies have been examined to use in energy storage and supply systems. In previous researches, many molecules such as methylcyclohexane, 17,20,21 ammonia, 7,8 sorbitol, 13 hydroquinone derivatives, [22][23][24][25][26][27][28] were tested as fuels. Among these molecules, methyl cyclohexane and ammonia have been intensively investigated, because they have high energy density and liquid state at room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation